Pengembangan Media Pembelajaran Ipa Berbasis Video Animasi Menggunakan Aplikasi Powtoon Materi Energi Dalam Kehidupan Sehari-Hari - Mutiara Mutiara; Nurkhairo Hidayati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to produce an animated video learning medium that is capable of energy material in everyday life for high school students. This research is a developmental research. Sampling techniques were random sampling with samples from 45 students from three schools. The research was conducted in three schools: Al-Mishbah Riau, YLPI P.Marpoyan, and PGRI Pekanbaru. This data is obtained from the student response sheets obtainable from the results of the limited qualification test of students. The results of this study have an average percentage of the three schools is 95%. Based on these results can be concluded that the development of learning media IPA based animation video using powtoon applications on energy materials in everyday life gets a good response from students so that it can be used in the learning process in the classroom.